2013
DOI: 10.1111/echo.12184
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Volume as Predictor of Valve Replacement and Cardiovascular Events in Patients with Asymptomatic Mild to Moderate Aortic Stenosis

Abstract: In asymptomatic patients with mild to moderate Aortic valve stenosis (AS), LA volume was not predictive of the combined endpoint of Aortic valve replacement, development of heart failure or cardiac death. AVA and presence of LV hypertrophy were the only predictors of events in multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(79 reference statements)
0
9
0
1
Order By: Relevance
“…21 Only 1 study has analyzed the outcome implications of indexed LAV in AS. 25 This report from the SEAS (Simvastatin and Ezetimibe in Aortic Stenosis) study included only asymptomatic patients with mild-to-moderate AS and failed to demonstrate an association between indexed LAV and the combined end point of AVR, heart failure, and cardiac death. 25 We report a strong association between severe LA enlargement and mortality in a large cohort of patients with AS.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…21 Only 1 study has analyzed the outcome implications of indexed LAV in AS. 25 This report from the SEAS (Simvastatin and Ezetimibe in Aortic Stenosis) study included only asymptomatic patients with mild-to-moderate AS and failed to demonstrate an association between indexed LAV and the combined end point of AVR, heart failure, and cardiac death. 25 We report a strong association between severe LA enlargement and mortality in a large cohort of patients with AS.…”
Section: Discussionmentioning
confidence: 92%
“…In a retrospective report of 622 patients with asymptomatic severe AS, LA diameter was reported to predict the occurrence of symptoms and mortality . Only 1 study has analyzed the outcome implications of indexed LAV in AS . This report from the SEAS (Simvastatin and Ezetimibe in Aortic Stenosis) study included only asymptomatic patients with mild‐to‐moderate AS and failed to demonstrate an association between indexed LAV and the combined end point of AVR, heart failure, and cardiac death .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left atrium (LA) enlargement has proven to be a powerful predictor of adverse outcomes in several disease entities. [9][10][11] However, no data are available correlating TZ-related LV dysfunction to baseline left atrial volume index (LAVI). Therefore, the aim of this single-center observational study was to investigate the relationship between baseline LAVI and cardiotoxicity development, and to test the hypothesis that baseline LA volume enlargement could predict TZrelated LV dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The development of HF symptoms in patients with AS has previously been demonstrated to be associated with degrees of AS severity and LV hypertrophy, 3 but HF symptoms in patients with AS often occur irrespective of AS severity and LVEF. On the other hand, it was recently reported that exercise performance is relevant for resting left atrium (LA) function, [4][5][6][7][8][9] and is also a quite important prognostic marker for patients with HF. 10,11 Changes in these structural and functional variables precede development of HF symptoms, are predictive of changes in clinical status.…”
mentioning
confidence: 99%